2012
DOI: 10.1088/0957-4484/23/45/455703
|View full text |Cite
|
Sign up to set email alerts
|

Observation of infrared-active modes in Raman scattering from topological insulator nanoplates

Abstract: Two infrared (IR)-active vibrational modes, observed at 93 and 113 cm(-1) in Raman scattering, are evidence of an inversion symmetry breakdown in thin (~10 nm) nanoplates of topological insulator Bi(2)Te(3) as-grown on SiO(2). Both Raman and IR modes are preserved after typical device fabrication processes. In nanoplates transferred to another SiO(2) substrate via contact printing, however, the IR modes are absent, and the Raman spectra are similar to those from bulk samples. The differences between as-grown a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
7
25
0
Order By: Relevance
“…Note that similar tellurium segregation has been reported for Bi-Te films [30] and for Sb 2 Te 3 films under strong laser irradiation [31]. Previously, the two vibrational modes at 2.8 and 3.67 THz were observed in Raman scattering for Bi 2 Te 3 nanoplates, but not in bulk crystals [32]. They were ascribed to IR modes and their appearance was interpreted as evidence of a parity breakdown in thin flakes of the topological insulator.…”
Section: Resultssupporting
confidence: 78%
“…Note that similar tellurium segregation has been reported for Bi-Te films [30] and for Sb 2 Te 3 films under strong laser irradiation [31]. Previously, the two vibrational modes at 2.8 and 3.67 THz were observed in Raman scattering for Bi 2 Te 3 nanoplates, but not in bulk crystals [32]. They were ascribed to IR modes and their appearance was interpreted as evidence of a parity breakdown in thin flakes of the topological insulator.…”
Section: Resultssupporting
confidence: 78%
“…The peak we attribute to a surface phonon is the weak feature which appears between the 2 and 1 2 modes at 159 cm -1 and 114 cm -1 for Bi2Se3 and Bi2Te3, respectively. This peak has been previously observed in thin films and few-monolayer samples of both compounds [16,18,31,32,33,34,35,36,37,38,39] and in single crystals of Bi2Se3 [39,40], but never 4 | P a g e before in bulk Bi2Te3. Note that these prior studies detected numerous other weak features in both compounds that were not observed in the present work.…”
supporting
confidence: 63%
“…The observation of extra Raman lines and, in particular, the lines we assign to surface phonons have been prevalently attributed in the literature to surface-induced symmetry breaking, which seemingly allows for scattering of nominally Raman forbidden, infrared-active modes [18,31,32,33,34,35,36,38,40]. For various reasons, we find such an interpretation to be incorrect.…”
Section: P a G Ementioning
confidence: 69%
See 1 more Smart Citation
“…Se atoms exhibit two different chemical environments. The chemical bonding between Bi and Se2 is of a pure covalent nature, while it is slightly ionic but still covalent in nature between Bi and Se1112627282930. As for the Bi 2 Se 3 compounds, O atoms preferentially replace Se at Se2 sites because O atoms at Se2 sites are more stable than the O atoms at Se1 sites, thus resulting in a measurable increase in the values of the lattice parameters of Bi 2 Se 3 .…”
Section: Discussionmentioning
confidence: 99%